2019
DOI: 10.3892/etm.2019.7637
|View full text |Cite
|
Sign up to set email alerts
|

Differential microRNA expression profile in the plasma of preeclampsia and normal pregnancies

Abstract: Preeclampsia is a common disease in pregnant women that can only be diagnosed from 20 weeks after fertilization. Developing early diagnosis markers is urgent and would be helpful in selecting appropriate treatment strategies. The present study aimed to identify the differential expression profiles of microRNAs in the plasma between patients with preeclampsia and normal pregnancies using microarray methods. Using quantitative polymerase chain reaction (qPCR), the differentially expressed microRNAs (miRNAs or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…miRNA recognizes the complementary binding sites of target gene for its seed regions which is approximately 6 nucleotides long in miRNA. Previously, numerous studies have provided the evidence of identification on miRNA derived from TE [30,31,33,34,36] and some of the miRNAs derived from TE had a strong correlation with human disease [46][47][48][49][50][51][52] as well as evolution [53][54][55][56][57]. Considering the many substantial aspects of TE, miRNAs derived from TE mimic the functions of TE.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA recognizes the complementary binding sites of target gene for its seed regions which is approximately 6 nucleotides long in miRNA. Previously, numerous studies have provided the evidence of identification on miRNA derived from TE [30,31,33,34,36] and some of the miRNAs derived from TE had a strong correlation with human disease [46][47][48][49][50][51][52] as well as evolution [53][54][55][56][57]. Considering the many substantial aspects of TE, miRNAs derived from TE mimic the functions of TE.…”
Section: Introductionmentioning
confidence: 99%
“…We also identi ed that miR-320a had potent clinical diagnostic value for EOPE using ROC curve, as con rmed by an area under ROC curve of 0.790, a speci city of 71.40% and a sensitivity of 70.00%. In support of these, a previous study has provided evidence that miR-320a is abnormally enhanced in PE patients, promising to be a therapeutic target for PE therapy [22]. It is well established that increased urinary protein excretion, MAP, UA and SCR levels during pregnancy are potent indexes for EOPE prediction [23][24][25][26].…”
Section: Discussionmentioning
confidence: 78%
“…The five most downregulated miRNAs were hsa-miRNA-188-3p, hsa-miRNA-211-5p, hiv1-miRNA-TAR-3p, hsa-miRNA-4432, and hsa-miRNA-4498. Functional analysis of differentially expressed miRNA in this study revealed that upregulated miRNAs were involved in the cell proliferation and migration, whereas downregulated miRNA in immune regulation, vascular development, and cancer pathology (cell cycle progression) [ 88 ]. Similar analysis was performed by Lip et al, but it concerned early-onset PE.…”
Section: Micrornasmentioning
confidence: 99%